Modulation of the Acher's limit by medium thickness in [FeCoB/ZnO]50 multilayers. Issue 1 (2nd January 2018) - Zhou, Xueyun; Yao, Dongsheng; Zhou, Liling; Hou, Cuiling
Abstract: This work investigates the high frequency characteristics of [FeCoB/ZnO]50 multilayers with different ZnO thickness. The results reveal that the Acher's limit of [FeCoB/ZnO]50 multilayers can be modulated by medium thickness. Increasing medium layer thickness is favorable for breaking through the Acher's limit. It is found that the differences of Acher's limit between multilayers and single layers are caused by magnetic interface anisotropy related to interface roughness and some unknown factor. Graphical Abstract: